Effects of Growth Hormones on Sprouting and Rooting of Jatropha Curcas l. Stem Cuttings - OF Adekola; IG Akpan (Journal of Applied Sciences and Environmental Management)
This study was conducted to assess the effect of growth hormone on sprouting and rooting ability of Jatropha curcas (L). Stem cuttings from mature plants were treated with two types of growth hormones: Naphthalene Acetic Acid and Indole-3-Butyric Acid while the untreated cuttings were used as control. The experiment was laid out as complete randomized design with three treatments replicated three times. The following parameters were evaluated : survival percentage, number of buds that sprouted, bud length, leaf number, and rooting parameters. Results showed that growth hormone application had no significant effect on survival and sprouting behaviour of J. curcas. The untreated cuttings (control) performed better than the hormone treated cuttings. However, in term of rooting behaviours, significant effect of treatment differences were observed at p < 0.05. Cuttings treated with IBA were found to root better than those of NAA, the control gave the best performance.